HUBUNGAN ANTARA DUKUNGAN SOSIAL ORANGTUA DAN KOMPETENSI INTERPERSONAL PADA SISWA KELAS X SMA NEGERI 2 SEMARANG - KHAIRINA WIDYA PH; Dian Ratna Sawitri (Faculty of Psychology, Diponegoro University, 2017)
The advancement of internet and technology developed rapidly in this digital era. 10th-grade of the senior high school students who are middle-aged adolescents begin to follow and use it as a contemporary trend that indirectly affects interpersonal competence. This study aims to determine the relationship between parents social support with interpersonal competence in 10th- grade students of Public Senior High School Two Semarang. The subject of this research is the 10th grade of Public Senior High School Two Semarang students. The sample of this research is 243 people, with cluster random sampling technique. The data were collected using Social Parental Support Scale (55 valid items; α = .94) and Interpersonal Competence Scale (25 valid items; α = .84) which have been tested on 61 students of 10th grade Public Senior High School Two Semarang. Simple regression analysis showed a significant positive correlation between parental social support and interpersonal competence, with correlation coefficient rxy = .46 (p <.001). That is, the higher the social support of parents, the higher the interpersonal competence, and vice versa. Social support of parents contributes 21.4% to interpersonal competencies. This research is expected to be a consideration for students, parents, and schools as well as supporting references for further researchers.